Proteomic Analysis of the Initial Oral Pellicle in Caries‐Active and Caries‐Free Individuals. Issue 4 (19th December 2018) - Trautmann, Simone; Barghash, Ahmad; Fecher‐Trost, Claudia; Schalkowsky, Pascal; Hannig, Christian; Kirsch, Jasmin; Rupf, Stefan; Keller, Andreas; Helms, Volkhard; Hannig, Matthias
Abstract : Purpose: To 1) elucidate individual proteomic profiles of the 3‐min biofilm of caries‐active and caries‐free individuals and 2) compare these proteomic profiles against the background of caries. Experimental design: The initial oral pellicle of 12 caries‐active and 12 caries‐free individuals is generated in situ on ceramics specimens. The individual, host‐specific proteomic profiles of this basic pellicle layer are analyzed by a chemical elution protocol combined with an elaborate mass spectrometry and evaluated bioinformatically. Results: A total of 1188 different proteins are identified. Additionally, 68 proteins are present in the profiles of all individuals, suggesting them as ubiquitously occurring base‐proteins of the initial human pellicle. Thereof, the single profiles exhibit high inter‐individual differences independent of their group affiliation, stating the initial pellicle to represent a rather "individual fingerprint". Quantitative analyses imply slight indication for 23 proteins potentially capable of counting for caries‐specific biomarkers. Conclusions and clinical relevance: The introduced protocol enables the individual analysis of minimal protein amounts and allows for highly precise characterizations and comparisons of individual proteomic profiles. The results contain a considerable higher extent of protein identifications and might serve as a base for future large scale analyzes to identify discrimination factors for the development of caries susceptibility tests.